Optimizing Children's Early Literacy Through Contextual Implementation of The Phonics Method in Rural Early Childhood Institutions - Ngura, Elisabeth; Fono, Yasinta Maria; Wea, Helena Rhero (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the Phonics method in improving early literacy in children aged 4-6 years. This study was designed using a qualitative approach with a case study method, conducted at Kober Peupado Malanuza. Data collection techniques used included observation, interviews, and documentation. Activities in data analysis included data collection, data reduction, data presentation, and drawing conclusions.The results of the study showed that consistent use of the Phonics method can improve children's ability to recognize letters, understand letter sounds, and read simple words. Based on observation data, there were 23.07% of children who could imitate the sounds (phoneme sounds) spoken by the teacher, 15.3% of children could pronounce sounds correctly, 46.15% of children could associate sounds with letters that correspond to the sounds heard, and 15.3% of children could combine letter sounds and then form words.The phonics method not only improves students' understanding of letters and letter sounds, but also helps them understand words and spell more accurately and effectively. The phonics method has also been shown to be effective in improving the reading skills of children with intellectual disabilities, dyslexia, and other students. Therefore, it can be an effective approach to improving reading skills (literacy) in early childhood.